Situs Menanga Solor Flores Timur: Jejak Islam di Nusa Tenggara Timur (NTT) - Muhamad Murtadlo (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
Solor Island, East Flores considered as one gate of the presence of three major religions (Islam, Catholicism, Christianity) in East Nusa Tenggara. The existence of Lohayong fort built by Portuguese (1566) became the beginning discussionabout history of religion in that area. This study was formulated to answer the question: whether Islam first present on the Solor Island? What kinds of evidencesthat prove of existence Islam on this island? Using archaeological and literature studies, the study concluded that there is some evidence like the presence of ulama Joe Pattiduri in Menanga at 13th century, the Fort of Menanga and the alliance of the five royal beach (Solor Watanlema). This facts also shows that Islam has been present before the Portuguese presence in the island. Keywords: Sites, Menanga, Watanlema Pulau Solor, Flores Timur menjadi saksi penting masuknya tiga agama besar (Islam, Katholik, Kristen) di Nusa Tenggara Timur (NTT). Keberadaan Benteng Lohayong yang dibangun Portugis (1566) menjadi awal diskusi masuknya agama di NTT. Penelitian ini dirumuskan untuk menjawab pertanyaan: apakah Islam lebih dahulu hadir di Pulau Solor? bukti apa saja yang bisa kita saksikan tentang Islam di Pulau Solor ini? Pendekatan kajian menggunakan studi arkeologi dan pustaka. Penelitian ini menyimpulkan bahwa ada beberapa bukti seperti hadirnya ulama Joe Pattiduri di Menanga abad 13, keberadaan Benteng Menanga dan Aliansi 5 kerajaan pantai Solor Watanlema. Fakta ini juga menunjukkan bahwa bahwa Agama Islam telah hadir sebelum Portugis hadir di Pulau Solor. Kata-kata Kunci: Situs, Menanga, Watan Lema